The oncologic safety and accuracy of indocyanine green fluorescent dye marking in securing the proximal resection margin during totally laparoscopic distal gastrectomy for gastric cancer: a retrospective comparative study - Byung Woo Yoon; Woo Yong Lee (World Journal of Surgical Oncology, 2022)
Abstract Background Securing the proximal resection margin in totally laparoscopic distal gastrectomy for gastric cancer is related to curability and recurrence, while reducing the operation time is related to patient safety. This study aimed to investigate the role of indocyanine green (ICG) fluorescent dye marking in totally laparoscopic distal gastrectomy, whether it is an oncologically safe and accurate procedure that can be conducted in a single centre. Methods The data of 93 patients who underwent laparoscopic-assisted distal gastrectomy (non-ICG group) or totally laparoscopic distal gastrectomy using ICG (ICG group) between 2010 and 2020 were retrospectively reviewed. To correct for confounding factors, a propensity score matching was performed. Results Proximal resection margin did not vary with the ICG injection site after the propensity score matching (lower ICG, 3.84 cm vs. lower non-ICG, 4.42 cm, p = 0.581; middle ICG, 3.34 cm vs. middle non-ICG, 3.20 cm; p = 0.917), while the operation time was reduced by a mean of 34 min in the ICG group (ICG, 239.3 [95% confidence interval, 220.1–258.5 min]; non-ICG, 273.0 [95% confidence interval, 261.6–284.4] min; p = 0.006). Conclusions ICG injection for securing the proximal resection margin in totally laparoscopic distal gastrectomy is an oncologically safe and accurate procedure, with the advantage of reducing the operation time of gastric cancer surgery while it has the benefit of locating the tumour or clips when it is impossible to locate the tumour during surgery due to the inability to perform an endoscopic examination or when it is hard to directly palpate the tumour or clips in the operating theatre; this can be performed at a single centre.